Unionsrechtliche Probleme der Überlassungspflicht für sortenrein erfasste Haushaltsabfälle zur Verwertung - Eine Untersuchung unter besonderer Berücksichtigung der EU-Regelungen für Daseinsvorsorgeleistungen - Suhl, Christian (Universitätsverlag Göttingen, 2018)
Waste is a commodity, and in particular the separately collected, single-variety waste from private households such as waste paper is a highly coveted commodity that public bodies responsible for waste management, i.e. the municipalities, and private sector waste management companies compete for. The German recycling law (KrWG), which came into force in 2012, allows for this waste according to §§ 17, 18 KrWG an exception to the general obligation to hand over the waste to the public bodies responsible for waste management. However, the exception is so narrow that the competent authorities, which are often the responsible bodies for waste management at the same time, can easily ban the collection of private companies. This restricts the European free movement of goods and infringes EU competition law. The present work highlights these restrictions and infringements and examines whether they can be justified, in particular, by the exemptions for Services of General Economic Interest (SGEI). Insofar as this does not succeed, an amendment of the relevant regulations of §§ 17 and 18 KrWG is proposed.